Repair of Hypoxanthine in DNA Revealed by DNA Glycosylases and Endonucleases From Hyperthermophilic Archaea - Lin, Tan; Zhang, Likui; Wu, Mai; Jiang, Donghao; Li, Zheng; Yang, Zhihui (Frontiers in Microbiology, 2021)
Since hyperthermophilic Archaea (HA) thrive in high-temperature environments, which accelerates the rates of deamination of base in DNA, their genomic stability is facing a severe challenge. Hypoxanthine (Hx) is one of the common deaminated bases in DNA. Generally, replication of Hx in DNA before repaired causes AT → GC mutation. Biochemical data have demonstrated that 3-methyladenine DNA glycosylase II (AlkA) and Family V uracil DNA glycosylase (UDG) from HA could excise Hx from DNA, thus triggering a base excision repair process for Hx repair. Besides, three endonucleases have been reported from HA: Endonuclease V (EndoV), Endonuclease Q (EndoQ) and Endonuclease NucS (EndoNucS), capable of cleaving Hx-containing DNA, thereby providing alternative pathways for Hx repair. Both EndoV and EndoQ could cleave one DNA strand with Hx, thus forming a nick and further initiating an alternative excision repair process for the follow-up repair. By comparison, EndoNucS cleaves both strands of DNA Hx-containing in a restriction endonuclease manner, thus producing a double-stranded break (DSB). This created DSB might be repaired by homologous recombination or by a combination activity of DNA polymerase, flap endonuclease 1 and DNA ligase. Herein, we reviewed the most recent advances in repair of Hx in DNA triggered by DNA glycosylases and endonucleases from HA, and proposed future research directions.